Central Bank of Nigeria and Nigerian Economy in the 21st Century - Osagioduwa, Lucky Ogbomo; Solomon, Ogudo Oakihena; Fumilayo, Oloye (The Journal of Accounting and Management, 2022)
This study investigated the extent to which the CBN conventions roles and monetary and fiscal policies formulated are adequate in scope and content towards addressing the Nigerian 21st century economic challenges. The research was conducted in two states in Nigeria, namely Delta, and Edo States respectively. Primary data were gotten through Five Likert Scale (SA, A, U, D, SD). A total of ninety-nine (99) copies of questionnaire where administered to junior and senior staff working in CBN Asaba and Benin branches from a study population of two hundred and fifty-four (254) and eighty-seven (87) was recovered. Qouta Random Technique (QRT) was adopted in the study. The hypotheses were tested employing the Pearson Product Moment Coefficient Correlation (PPMCC) and the Kendall’s tau-b Coefficient Correlation (KBCC). The result of the analysis revealed that there is negative statistical relationship between the conventional CBN activities (roles) and improvement in Nigeria 21st century economy, it was also discovered that there is significant positive relationship (.991 and .990 respectively) between 21st century oriented policy formulations by the CBN and growth in the Nigerian 21st century economy. It was realized from the study that attainment of the CBN cardinal role (financial and exchange rate stability) would result in 21st century economic growth by 0.1percent. The study therefore recommends that the CBN should formulate 21st century problems addressing fiscal and monetary policies in Nigeria. The policies should be strategic and Nigeria base without any repetition of the monetary and fiscal policies in existence in advanced nations being that the Nigerian 21st century economy dilemma is different.